Vitamin D [25(OH)D] and 1,25(OH)2D 2 serum concentrations in patients tested at 3 the Charlotte Maxeke Johannesburg 4 Academic Hospital - Botha, Sunet (My University, 2022)
Introduction: There has been a significant increase in vitamin D [25(OH)D] testing worldwide in recent years. However, interpretation is confounded by the lack of data to determine appropriate cut-off levels to define Vitamin D deficiency, insufficiency and sufficiency in the South African population. Aims: To describe the number of tests, concentrations for 25(OH)D and 1,25(OH)2D in adults (≥ 18 years), characteristics of those tested and to determine the 25(OH)D concentration at which parathyroid hormone increases (PTH threshold). Methods: Data was extracted for 25(OH)D and 1,25(OH)2D tests, from the National Health Laboratory Services data warehouse for Charlotte Maxeke Johannesburg Academic Hospital from 2015 to 2017. Results were categorized by age, sex and race. Vitamin D status was described using National Academy of Medicine guidelines. The PTH threshold was determined by LOWESS plots. Results: 25(OH)D and 1,25(OH)2D tests increased, with no change in median concentrations over time. Black Africans (6.7%) had the highest prevalence of VDD. Males had significantly lower 25(OH)D values (p <0.001) and a higher proportion of VDD (p =0.009). Younger patients (<30 years; 7.9%) and elderly (>74 years; 10.5%) Black Africans had highest prevalence of VDD. The PTH threshold differed by race group. Conclusions: Clear testing guidelines are needed to curb test overutilization. Further work is required to understand the appropriate cut-off levels to define VDD in the populations.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Medicine in Clinical Pathology to the Faculty of Health Sciences, School of Pathology, University of Witwatersrand,.Johannesburg, 2020